Rationale and design of randomized non-inferiority clinical trial to compare the safety and efficacy of ticagrelor monotherapy with dual antiplatelet therapy in chronic coronary syndrome patients post percutaneous coronary intervention (TICALONE-TAHA10 Protocol) - Seyed Alireza Mirhosseini; Mohammadreza Akbari; Davar Aldavood; Hooyar Zarifkar; Armin Attar; Javad Kojuri (PLoS ONE, 2025)
Background Despite the wide variety of antiplatelet regimens and durations, the optimal treatment approach for chronic coronary syndrome (CCS) patients remains a subject of ongoing debate. While current guidelines recommend dual antiplatelet therapy (DAPT) with aspirin and clopidogrel, the development of drug-eluting stents (DES) and more potent agents has sparked interest in shorter DAPT regimens, followed by P2Y12 inhibitor monotherapy, as a potential alternative. Recent trials and meta-analyses have shown that this approach may provide similar protection against thrombotic events with reduced bleeding risk. Despite promising data, the safety and efficacy of Ticagrelor monotherapy specifically in CCS patients have not been rigorously tested in randomized trials. Methods TICALONE is a non-inferiority, two-arm, double-blinded, randomized controlled clinical trial designed to evaluate the safety and efficacy of ticagrelor monotherapy compared to DAPT in CCS patients following PCI. Eligible patients undergoing PCI with drug-eluting stents will be randomly assigned to receive either conventional DAPT (aspirin and clopidogrel) or ticagrelor monotherapy for six months. Follow-up visits will be conducted at 1, 3, 6, and 12 months post-PCI to assess efficacy and safety endpoints. The primary efficacy endpoint is a composite endpoint of cardiac death, myocardial infarction, stroke, stent thrombosis, and the need for revascularization. The primary safety endpoint is the occurrence of Bleeding Academic Research Consortium (BARC) type 3 or 5 bleeding events. The secondary endpoints include components of the primary efficacy endpoint, any bleeding event (BARC type 1–5), and all-cause mortality. Ancillary endpoints are other adverse events including dyspnea, drug adherence, and reaction. All endpoints will be monitored by a Data Safety Monitoring Board (DSMB) and Trial Management Committee (TMC). Statistical analysis and reporting of trial results will follow the estimand framework. Kaplan-Meier estimates will be used to assess event rates, while the log-rank test and Cox regression analysis will be employed to compare safety and efficacy outcomes between the groups. Discussion This trial may serve as a crucial step toward eliminating aspirin from post-PCI regimens, specifically in CCS patients. By comparing the safety and efficacy of Ticagrelor monotherapy with the conventional DAPT regimen and addressing potential risks of aspirin-free therapy and adverse events like dyspnea, this study could offer valuable insights into the possibility of P2Y12 monotherapy’s safe adoption in this population. Trial registration TICALONE is registered at https://clinicaltrials.gov/ with the identifier NCT06509893.